PROFIL USAHA MINYAK ATSIRI PALA UD. WIDIA MANDIRI DI DESA TREMAN - Paris Loziner Edison Sirait; Ventje V. Rantung; Lyndon R.J. Pangemanan; Jean F.J. Timban (COCOS, 2013)
ABSTRACTThe objective of this research was to determine the profile of the business nutmegessential oil. This study used primary data obtained through interview techniques directly tobusiness owners using a list of questions were primarily production and cost. The methodanalysis was a descriptive analysis and presented in tables. Other analysis was costs, revenues,profits, and ratio of R/C.The results of this research indicated that the efforts of nutmeg essential oil "UD. WidiaMandiri" was still considered home industry. The capital came from their own family capital.The raw materials used were nutmeg for one-time distillation process as much as 250 kg with ayield of 7%. For one month only produced a one-time distillation process and products at a sizeof 702 bottles of 10 ml, and 200 bottles of 60 ml.The nutmeg essential oil distillation enterprise employed only 2 employees and one labor.The product was marketed in the industry itself and at some souvenir shops in Manado city,namely: Merciful Building, Kawanua Souvenir, and Manado Souvenir. This effort received aprofit of Rp. 1.806.500,00 for a month of production.Based on this research it can be concluded that the management is still very simple. Therehas been no attempt to distinguish the budgetary accounting industry and household budget. Theresults of the analysis of the ratio of R / C was 1.1 indicating that the business is feasible to bedeveloped.